Dextran sulphate-induced tau assemblies cause endogenous tau aggregation and propagation in wild-type mice. Issue 2 (8th July 2020) - Masuda-Suzukake, Masami; Suzuki, Genjiro; Hosokawa, Masato; Nonaka, Takashi; Goedert, Michel; Hasegawa, Masato
Abstract: Accumulation of assembled tau protein in the central nervous system is characteristic of Alzheimer's disease and several other neurodegenerative diseases, called tauopathies. Recent studies have revealed that propagation of assembled tau is key to understanding the pathological mechanisms of these diseases. Mouse models of tau propagation are established by injecting human-derived tau seeds intracerebrally; nevertheless, these have a limitation in terms of regulation of availability. To date, no study has shown that synthetic assembled tau induce tau propagation in non-transgenic mice. Here we confirm that dextran sulphate, a sulphated glycosaminoglycan, induces the assembly of recombinant tau protein into filaments in vitro . As compared to tau filaments induced by heparin, those induced by dextran sulphate showed higher thioflavin T fluorescence and lower resistance to guanidine hydrochloride, which suggests that the two types of filaments have distinct conformational features. Unlike other synthetic filament seeds, intracerebral injection of dextran sulphate-induced assemblies of recombinant tau caused aggregation of endogenous murine tau in wild-type mice. AT8-positive tau was present at the injection site 1 month after injection, from where it spread to anatomically connected regions. Induced tau assemblies were also stained by anti-tau antibodies AT100, AT180, 12E8, PHF1, anti-pS396 and anti-pS422. They were thioflavin- and Gallyas-Braak silver-positive, indicative of amyloid. In biochemical analyses, accumulated sarkosyl-insoluble and hyperphosphorylated tau was observed in the injected mice. In conclusion, we revealed that intracerebral injection of synthetic full-length wild-type tau seeds prepared in the presence of dextran sulphate caused tau propagation in non-transgenic mice. These findings establish that propagation of tau assemblies does not require tau to be either mutant and/or overexpressed. Abstract : We demonstrate that tau filaments assembled from recombinant tau protein and dextran sulphate differ from those assembled using heparin. Intracerebral injection of tau filaments induced by dextran sulphate into wild-type mice caused seeding of endogenous murine tau, followed by spreading to distinct brain areas in a time-dependent manner. Graphical Abstract: